The Serbian Environmental Inform ENVIRONMENT INFORMATION SYSTEM IN LUHMANN’S THEORY OF SOCIETY: Application of visualization and effective communication on the example of the Serbian Environmental Protection Information System from the point of view of Luman’s social theory - Veljković, Nebojša; Perunovic Culic, Tamara (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2023)
Abstract: The information technology revolution has among else led to the accelerated growth of the quantity and availability of accessible data as an indicatior of interactions in the ecosocial system. This study describes how atoms producing pollution translate into bites and digitaly transform into indicators and information. Through the example of the Serbian Environmental Information System, the study also shows how visualisation and effective comunication are applied from the viewpoint of Luhmann’s theory of society. According to Luhmann’s theory, the society consists of closed systems of independent communications which continuously reproduce and develop by repeating their operations. The Serbian Environmental Information System represents a subcategory of the Luhmann’s scientific subsystem and offers an answer to the question why there are, on the one hand, so many scientific facts on pollution, and on the other so few environmental measures that are undertaken. The answer lies in the fact that environmental pollution indicators belong to one social subsystem, while measures are expected to be taken within another social subsystem - law and economy, where each of them strives to preseve uniqueness and remain self-existent. According to Luhmann’s social framework relevant for environmental protection, communication is a social system’s response to environment that offers communicology a chance to examine the phenomena of environmental concerns in a more critical and detailed manner.